Comparison of mammosphere formation from breast cancer cell lines and primary breast tumors - Wang, Rong; Lv, Qing; Meng, Wentong; Tan, Qiuwen; Zhang, Shu; Mo, Xianming; Yang, Xiaoqin (Journal of Thoracic Disease, 2014)
Background: Breast cancer stem cells (BCSCs) can be enriched by culturing of cells in non-adherent nondifferentiating conditions. However, culturing mammospheres from primary breast tumors are costly and difficult to control. In order to overcome problems associated with using primary human tissues, continuous breast cancer cell lines have been developed from various sources. Methods: In this study, a luminal subtype breast cancer cell line MCF-7 and a basal subtype cell line MDAMB- 231 were chosen. We explored the optimal culturing system for BCSCs from the two cell lines and primary breast tumors. Then, mammosphere formation efficiency (MFE), CD44+/CD24–/lowESA+Lin– cell proportion in mammospheres, and tumorigenecity of mammospheres generated from the two breast cancer cell lines and primary breast tumors were compared. Results: Enzymatic digestion of 60 mins and the addition of B27 to the culture medium were optimal for mammosphere culturing. Mammospheres could be formed in all the three cells, in which MCF-7 had the highest MFE. After 3 weeks culture, CD44+/CD24–/lowESA+Lin– cell proportion in mammospheres from MCF-7, MDA-MB-231 cells and primary breast tumors was 95.0%±2.5%, 82%±22% and 21.5%±1.0%, respectively. A total of 1,000 cells from MCF-7, MDA-MB-231 mammospheres but not primary mammospheres were tumorigenic. Conclusions: This study validates the use of breast cancer cell lines as models to elucidate the nature of BCSCs.